Modification of blood pressure in postmenopausal women: role of hormone replacement therapy - Cannoletta M; Cagnacci A (Dove Medical Press, 2014)
Marianna Cannoletta, Angelo Cagnacci Institute of Obstetrics and Gynecology, Department of Medical and Surgical Sciences of the Mother, Child and Adult, University of Modena and Reggio Emilia, Modena and Reggio Emilia, Emilia-Romagna, Italy Abstract: The rate of hypertension increases after menopause. Whether estrogen and progesterone deficiency associated with menopause play a role in determining a worst blood pressure (BP) control is still controversial. Also, studies dealing with the administration of estrogens or hormone therapy (HT) have reported conflicting evidence. In general it seems that, despite some negative data on subgroups of later postmenopausal women obtained with oral estrogens, in particular conjugated equine estrogens (CEE), most of the data indicate neutral or beneficial effects of estrogen or HT administration on BP control of both normotensive and hypertensive women. Data obtained with ambulatory BP monitoring and with transdermal estrogens are more convincing and concordant in defining positive effect on BP control of both normotensive and hypertensive postmenopausal women. Overall progestin adjunct does not hamper the effect of estrogens. Among progestins, drospirenone, a spironolactone-derived molecule, appears to be the molecule with the best antihypertensive properties. Keywords: hormone replacement therapy, estrogen, progestin, blood pressure, menopause, hypertension